2015
DOI: 10.3390/life5010888
|View full text |Cite
|
Sign up to set email alerts
|

Nitrogen Starvation Acclimation in Synechococcus elongatus: Redox-Control and the Role of Nitrate Reduction as an Electron Sink

Abstract: Nitrogen starvation acclimation in non-diazotrophic cyanobacteria is characterized by a process termed chlorosis, where the light harvesting pigments are degraded and the cells gradually tune down photosynthetic and metabolic activities. The chlorosis response is governed by a complex and poorly understood regulatory network, which converges at the expression of the nblA gene, the triggering factor for phycobiliprotein degradation. This study established a method that allows uncoupling metabolic and redox-sign… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 31 publications
(21 citation statements)
references
References 52 publications
0
21
0
Order By: Relevance
“…A decrease in amino acid pools with a corresponding increase in AKG is consistent with an NADPH deficit in ΔrpaA cells. Additionally, elevated AKG can activate a nitrogen-starvation transcriptional response in cyanobacteria (36,37), and although these cells were not nitrogen-starved, we found that elevated AKG levels in ΔrpaA were accompanied by this transcriptional response ( Fig. S3 and SI Text).…”
Section: Darkness Initiates Pigmentation Changes and Rapid Cell Deathmentioning
confidence: 68%
“…A decrease in amino acid pools with a corresponding increase in AKG is consistent with an NADPH deficit in ΔrpaA cells. Additionally, elevated AKG can activate a nitrogen-starvation transcriptional response in cyanobacteria (36,37), and although these cells were not nitrogen-starved, we found that elevated AKG levels in ΔrpaA were accompanied by this transcriptional response ( Fig. S3 and SI Text).…”
Section: Darkness Initiates Pigmentation Changes and Rapid Cell Deathmentioning
confidence: 68%
“…Reduction in the amount of NblB under starvation suggests an active signal for proteolysis of this protein when the level of phycobilisome pigments decreases. In contrast, the nblA gene, encoding a small protein essential for phycobilisome degradation, is highly induced under nutrient starvation (Schwarz and Grossman, ; Sauer et al ., ; Luque et al ., ; van Waasbergen et al ., ; Osanai et al ., ; Sendersky et al ., ; Lahmi et al ., ; Salinas et al ., ; Zabulon et al ., ; Leganes et al ., ; Klotz et al ., ).…”
Section: Resultsmentioning
confidence: 97%
“…To get a clearer picture on the role of Slr1658 in the Synechocystis 6803 regulatory network we selected a number of representative transcripts and stress conditions for further analysis. In addition to pgr5 we tested the iron‐stress inducible transcript isiA (Dühring et al ., ) and the nitrogen limitation inducible nblA transcript (Klotz et al ., ). These three genes exhibited significantly altered expression profiles during Fe limitation (Table ).…”
Section: Resultsmentioning
confidence: 97%